Changes in epicardial and visceral adipose tissue depots following bariatric surgery and their effect on cardiac geometry - Henry, J. A.; Abdesselam, I.; Deal, O.; Lewis, A. J.; Rayner, J.; Bernard, M.; Dutour, A.; Gaborit, B.; Kober, F.; Soghomonian, A.; Sgromo, B.; Byrne, J.; et al. (Frontiers in Endocrinology, 2023)
Introduction Obesity affects cardiac geometry, causing both eccentric (due to increased cardiac output) and concentric (due to insulin resistance) remodelling. Following bariatric surgery, reversal of both processes should occur. Furthermore, epicardial adipose tissue loss following bariatric surgery may reduce pericardial restraint, allowing further chamber expansion. We investigated these changes in a serial imaging study of adipose depots and cardiac geometry following bariatric surgery. Methods 62 patients underwent cardiac magnetic resonance (CMR) before and after bariatric surgery, including 36 with short-term (median 212 days), 37 medium-term (median 428 days) and 32 long-term (median 1030 days) follow-up. CMR was used to assess cardiac geometry (left atrial volume (LAV) and left ventricular end-diastolic volume (LVEDV)), LV mass (LVM) and LV eccentricity index (LVei – a marker of pericardial restraint). Abdominal visceral (VAT) and epicardial (EAT) adipose tissue were also measured. Results Patients on average had lost 21kg (38.9% excess weight loss, EWL) at 212 days and 36kg (64.7% EWL) at 1030 days following bariatric surgery. Most VAT and EAT loss (43% and 14%, p<0.0001) occurred within the first 212 days, with non-significant reductions thereafter. In the short-term LVM (7.4%), LVEDV (8.6%) and LAV (13%) all decreased (all p<0.0001), with change in cardiac output correlated with LVEDV (r=0.35,p=0.03) and LAV change (r=0.37,p=0.03). Whereas LVM continued to decrease with time (12% decrease relative to baseline at 1030 days, p<0.0001), both LAV and LVEDV had returned to baseline by 1030 days. LV mass:volume ratio (a marker of concentric hypertrophy) reached its nadir at the longest timepoint (p<0.001). At baseline, LVei correlated with baseline EAT (r=0.37,p=0.0040), and decreased significantly from 1.09 at baseline to a low of 1.04 at 428 days (p<0.0001). Furthermore, change in EAT following bariatric surgery correlated with change in LVei (r=0.43,p=0.0007). Conclusions Cardiac volumes show a biphasic response to weight loss, initially becoming smaller and then returning to pre-operative sizes by 1030 days. We propose this is due to an initial reversal of eccentric remodelling followed by reversal of concentric remodelling. Furthermore, we provide evidence for a role of EAT contributing to pericardial restraint, with EAT loss improving markers of pericardial restraint.